Virtual Reality in Tourism : A Research Note - Sabari Shankar, R.; Koshy, Elizabeth Renju; Mathew, Sonia Katherin (Prabandhan: Indian Journal of Management, 2022)
Technology inclusions have been deriving disruptive changes in the tourism industry. The most sought-after digital tool – virtual reality (VR) – has been highly preferred by destination marketers in formulating their marketing strategies and executions and branding their destinations. Though VR inclusion started early, the pandemic crisis has added effectiveness to the vibrance of the industry’s offerings. However, the research of VR inclusions in tourism marketing needs wider evidence that would eventually facilitate the thereof in identifying and understanding of the emerging tourists’ micro-segments based on their motives, duality of destination management and branding, and the relevance for conceiving memorable experiences. This research note indicated three such critical aspects – VR in upscaling tourism, VR as a marketing strategy for sustainability, and VR as reality or reality for tourists. The note also indicated the major areas that can be researched from the given perspectives of VR for tourism marketing and destination branding.